ANALISIS DATA SISTEM MANAJEMEN PENGADUAN MASYARAKAT BERBASIS WEB PADA KEMENTERIAN SOSIAL ABIYOSO CIMAHI - Junaedi; Rini Tisnawati; Candra Mecca Sufyana (INFOKOM (Informatika & Komputer), 2025)
Website-based community complaint system is an alternative to facilitate the community in improving the efficiency of public services at the ministry of social center abiyoso cimahi. With this website-based complaint system, it is hoped that the community will find it easier to access the complaint site. This study aims to analyze the complaint data generated by the system in order to provide more effective and efficient services to facilitate the community in making complaints. With this as a researcher, I use qualitative research methods including descriptive data collection, and data exploration using data mining. the results of this study show that most of them are related to social services and accessibility for people with disabilities. The implementation of a web-based complaint system has increased the effectiveness, efficiency and transparency in handling complaints. Recommendations from this research include optimizing the system with artificial intelligence for complaint classification and developing mobile applications to increase accessibility for the wider community.